STUDI LITERATUR : ANALISIS PEMANFAATAN TES WAIS DALAM DIAGNOSIS ASESMEN KLINIS - Agustina Nur Rahmah; Aas Nurasiah; Aliyah Ardhana Riswari (Flourishing Journal, 2022)
Abstract: Intelligence in general is a general ability to acquire skills that contain various components, to reveal individual abilities, intelligence test instruments are usually used. One example of an intelligence test, is the WAIS test (Wechsler Adult Intelligence Scale). The WAIS test is presented individually and requires special skills for its presentation. The purpose of this literature study is to determine the use of the Wais test tool in the diagnosis of clinical assessment because Wais has superior competence in assessing individual cognitive abilities. We raised this topic because the advantages of the WAIS test are not only measuring the level of intelligence, but also being a diagnostic tool for clinical assessments. WAIS capabilities can be used to measure individual intelligence, neuropsychological, psychological assessment, and other diagnostic functions. The research method used in this research is literature study. Literature study is a synonym for literature review, literature review, theoretical basis, theoretical study, and literature review. The data used in this study is secondary data, the data of this research comes from the results of previous studies that have been published through journal articles, books, and continuous references to the research topic. In this literature study, it was found that the use of the Wechsler Adult Intelligence Scale (WAIS) test for clinical diagnosis includes, namely, being used to see indications of disease in psychiatric patients, screening for Alzheimer's Dementia (AD), a tool to see comparisons between people with beta thalassemia minor. with normal people, and as a test for trichotillomania Keywords: Intelligence, WAIS, Clinical Assessment. Abstrak: Intelegensi secara umum merupakan suatu kemampuan umum untuk memperoleh kecakapan yang mengandung berbagai macam komponen, untuk mengungkapkan kemampuan individu biasanya digunakan instrumen tes intelegensi. Salah satu contoh tes intelegensi, adalah tes WAIS (Wechsler Adult Intelligence Scale). Tes WAIS disajikan secara individual dan membutuhkan kemampuan khusus untuk penyajiannya. Tujuan dari studi literatur ini adalah mengetahui pemanfaatan alat tes wais dalam diagnosis asesmen klinis karena Wais memiliki kompetensi dalam menilai kemampuan kognitif individu yang sangat unggul. Kami mengangkat topik ini karena keunggulan dari tes WAIS tidak hanya mengukur tingkat kecerdasan saja, tetapi juga menjadi alat diagnosis bagi asesmen klinis. Kemampuan WAIS dapat digunakan untuk mengukur kecerdasan individu, neuropsikologis, asesmen psikologi, dan fungsi diagnostik lainnya. Metode penelitian yang digunakan dalam penelitian ini adalah studi pustaka. Studi pustaka merupakan sinonim dari kajian pustaka, tinjauan pustaka, landasan teori, kajian teoritis, dan telaah pustaka. Data yang digunakan dalam penelitian ini adalah data sekunder, data-data penelitian ini berasal dari hasil-hasil dari penelitian sebelumnya yang sudah di publish melalui artikel jurnal, buku, dan rujukan yang berkesinambungan dengan topik penelitian. Dalam studi literatur ini didapatkan hasil bahwa pemanfaatan tes Wechsler Adult Intelligence Scale (WAIS) untuk diagnosa klinis diantaranya yaitu, digunakan untuk melihat indikasi penyakit pada pasien psikiatri,, skrining adanya Alzheimer's Dementia (AD) , alat untuk melihat perbandingan antara orang dengan thalasemia beta minor dengan orang yang normal, dan sebagai alat untuk mengetes dari gangguan trikotilomania Kata kunci: Intelegensi, WAIS, Diagnosis Asesmen Klinis